Identifying Platforms and Methods in the Development of Geographic Information Systems (GIS) in Indonesia: Systematic Literature Review - Zulfikar, Muhammad Naufal Zulfikar; Kaila Yusri Salsabilla; Daffa Fadhilah Al Hafizh; Fitroh (LPPM & Fakultas Teknologi Informasi UNSAP, 2024)
This research aims to develop a comprehensive understanding of the platfroms and methods used in developing Geographic Information Systems (GIS) in Indonesia. Methods of Systematic Literature Analysis are involved to identify commonly used platforms, design method, and development method for GIS development. The data used came from journals published between 2018 and 2023, 82 pieces of literature were found from Publish or Perish and Google Scholar. The research results show that Waterfall method is the most widely used for development method as many as 25 journals use this method, for design method UML (Unified Modeling Language) is the most often used in total 52 journals using this method, and the platforms that are most frequently used or popular in the last 5 years in GIS development in Indonesia is Web-based as many as 54 out of 82 journals that we reviewed. This article provides valuable insights for practitioners, researchers, and decision makers who are interested in developing and utilizing GIS in Indonesia